If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 40 * 23 = 3x + -13 * 10 Multiply 40 * 23 x + 920 = 3x + -13 * 10 Reorder the terms: 920 + x = 3x + -13 * 10 Multiply -13 * 10 920 + x = 3x + -130 Reorder the terms: 920 + x = -130 + 3x Solving 920 + x = -130 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 920 + x + -3x = -130 + 3x + -3x Combine like terms: x + -3x = -2x 920 + -2x = -130 + 3x + -3x Combine like terms: 3x + -3x = 0 920 + -2x = -130 + 0 920 + -2x = -130 Add '-920' to each side of the equation. 920 + -920 + -2x = -130 + -920 Combine like terms: 920 + -920 = 0 0 + -2x = -130 + -920 -2x = -130 + -920 Combine like terms: -130 + -920 = -1050 -2x = -1050 Divide each side by '-2'. x = 525 Simplifying x = 525
| x+40=23 | | e/7-=8 | | P=500+10(100000) | | qxh=-36 | | -7(-2x+1)-3x= | | qh=-36 | | (3x+2y)(4x-2y)= | | 7=x+(-5) | | 5x+20y=250 | | 5x+5(5x+3)=74 | | 36x^2+15x-3=270 | | -7(x+3)=56 | | 550=(175)(7)+b | | -9=x-25 | | -2=x-723 | | 4x/x=16 | | -3(4x+1)=69 | | 1-8=623+x | | 58-6-x+51-3=55 | | -14-x=20 | | 0.5x-7=1.5x-1 | | 5e^2x+16=41 | | x+2x+3x=150 | | 4x-5x+x=11x-3 | | 3/5/9 | | (3/2)-4x=(1/2) | | -2(4x-1)=5(2x-5) | | -11x+5=14x | | 3/5x9 | | x-23=-78 | | x(7)=(17)(8) | | 170+0.25=365 |